PENGGUNAAN METODE PESAWAT BERTANYA UNTUK MENINGKATKAN PRESTASI DAN MOTIVASI BELAJAR SISWA KELAS VII-F SMP NEGERI 1 WELERI KABUPATEN KENDAL - Hidayati, Juni (Dinamika Pendidikan, 2012)
The purpose of this research is to improve students' academic achievement and motivation using the plane asked. Action research was conducted at SMP Negeri 1 Weleri with research subjects class VII-F by 30 students. Implementation research is conducted in two cycles. Data collecting technique consists of two data, test data and non-test. The results showed learning by using the asking plane can improve student achievement. This is evidenced by the increase in value by 53% a write test, and the achievement of the KKM (Minimum Completences Criteria) on aspects of an increase of 40% is exceeded. Learning process by using the asking plane capable of increasing student motivation VII-F class. Indications of this increase can be seen from the data increases in value by 36,7% motivation. Development of student’s behavior increase. The student’s abily to respond and answer the questions rose by 3,33%. Student activity in listening increase of 3,33%. Student skills in presenting the material to rise by 3,34%. While the student activity in discussion groups experienced increase of 0,83%.